Fucosylated chondroitin sulfate diversity in sea cucumbers: A review - Pang Myron; Shafiquzzaman Siddiquee; Sujjat Al Azad (Elsevier, 2014)
Fucosylated chondroitin sulfate (FucCS) is structurally distinct glycosaminoglycans found from the sea cucumber body wall consisted of chondroitin sulfate type backbone with attached sulfated or no sulfated fucose side chain. Structurally this compound plays an important role in maintaining the body wall integrity and possesses a wide spectrum of biological activities. Recently several glycosaminoglycans’ structures have been solved to elucidate its physicochemical activity. The purpose of this review paper is to elaborate existing structural properties and functions, reporting over 30 years and systematically discussion herein.